Evaluating the performance of agricultural tractor engine using cottonseed oil biodiesel - Adnan, Fattah Khalid; Muhamad, Mat Noor; Abdulrahman, Ribwar Kermanj; Badruddin, Irfan Anjum; Kamangar, Sarfaraz (Semarak Ilmu Publishing, 2024)
The energy demand has been significantly increasing around the world in the last century. Conventional fossil fuels as one of the sources has been highly demanded due to its negative environmental effect. The growing demand for energy stimulated the development of renewable and eco-friendly alternative energy sources. Produced from vegetable oils and animal fats, biodiesel is a renewable, sustainable, and biodegradable fuel. It can be used as an alternate fuel to conventional diesel (CD) in compression ignition (CI) engines. The Belarus 920 tractor, with a maximum output of 74.5kW, was put through a Power Take Off (PTO) test in this study to assess its performance and emission components when fueled with conventional petroleum diesel, B20, B50, and B100 of Cotton Seed Oil Biodiesel (CSOME). The performance results showed that the power and Break Thermal Efficiency (BTE) fell, while the BSFC improved, when the tractor was fueled with neat CSOME and its mixes.